Bianca Looks from above the Book: Readings on the Margin of Bruno Schulz’s Ex-Libris for Stanisław Weingarten - Maszewski, Zbigniew (Text Matters: A Journal of Literature, Theory and Culture, 2012)
The bookplate which Bruno Schulz designed in 1919 for his friend, Stanisław Weingarten, anticipates the motifs of his later literary work: a book, the Book, a collection of books reflecting the collector’s preferences but dependent on the laws undermining the notions of authorship and ownership. Standing on the margin of the artistic and literary scene, Pierrot/Schulz acknowledges the relatedness of his and Weingarten’s “private” vision with the recurrent, universal themes of world art and literature. The scene designed for the emblem of Weingarten’s library demonstrates Schulz’s awareness that the pleasure of discovering spaces of textual cross-fertilizations belongs to the realm of discoveries made by “standard” narratives of psychoanalysis. The scene also demonstrates Schulz’s readiness to imaginatively play with that awareness. The essay traces correspondences between the elements of the 1919 Pierrot ex-libris and the books from Weingarten’s collection which, with time, included and gave privileged position to the works of Bruno Schulz. Among the authors referred to are Rainer Maria Rilke, Alfred Kubin, and Jules Laforgue (in the critical appreciation of Jan Szarota).